Pelestarian Nilai-Nilai Luhur dalam Tradisi Jawa di Masyarakat Desa Bukit Rejo Kab. Simalungun Sumatera Utara - Gusti Aprila Pasaribu; Luhfiah Malaya Alfa; Riswanda Pratama Pane (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The mostly Muslim Javanese population of Bukit Rejo has struggled to let go of their Javanese customs and culture. Sometimes there may be tasks to be done in this custom and civilization. The people of Bukit Rejo really respect Javanese customs and culture. The idea of developing strong relationships and friendships among villagers is one of these customs and cultures. If we take a closer look at Javanese culture and traditions, especially with regard to their goals and methods of implementation, we may not be fully aware of a large number of Javanese customs. This research analyzes Javanese traditions in Bukit Rejo village, and understands their role in community life, as well as identifying factors that influence their sustainability.